Socio-economic development in the 21st century - Sen, Raj Kumar (Ed.); Basu, Ratan Lal (Ed.) (New Delhi Deep and Deep, 2001)
This is an edited volume consisting of selected papers presented in the IIDS 4th International Conference on Development and Future Studies held in University Kebangsaan, Malaysia.It contains 28 articles distributed over 4 parts. The first part deals with
Keywords: Economics-Sociolgoical aspects; Economic development; Rural development